2021
DOI: 10.3390/ijms222111602
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolones Suppress TGF-β and PMA-Induced MMP-9 Production in Cancer Cells: Implications in Repurposing Quinolone Antibiotics for Cancer Treatment

Abstract: Background: Fluoroquinolones (FQs) are potent antimicrobials with multiple effects on host cells and tissues. Although FQs can attenuate cancer invasion and metastasis, the underlying molecular mechanisms remain unclear. Matrix metalloproteinase-9 (MMP-9) has functional roles in tumor angiogenesis, invasion, and metastasis, and is associated with cancer progression and poor prognosis, suggesting that inhibitors of MMP-9 activity and transcription are prime candidates for cancer therapy. Despite numerous precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Fluoroquinolones may stop TGF-β biosynthesis by increasing the amount of endoplasmic cAMP and blocking TGF-β receptors. 179 The current trial was in agreement with Kan et al who stated that fluoroquinolones like gemifloxacin may interfere with NF-κB activation and cytokine-driven cell infiltration, as indicated by a reduced concentration of TNF-α, IL-8, and VEGF in the assessment of skin wound repair and regeneration 180 Furthermore, encouraging research signifies that gemifloxacin mitigates TNF-α-mediated NF-κB stimulation, lymphocyte penetration, and recruitment. 181 In another investigation, gemifloxacin also modified the immune response utilizing normal adult monocytes by suppressing monocytic liberation of IL-1β, IL-6, and TNF-α.…”
Section: ■ Discussionsupporting
confidence: 86%
“…Fluoroquinolones may stop TGF-β biosynthesis by increasing the amount of endoplasmic cAMP and blocking TGF-β receptors. 179 The current trial was in agreement with Kan et al who stated that fluoroquinolones like gemifloxacin may interfere with NF-κB activation and cytokine-driven cell infiltration, as indicated by a reduced concentration of TNF-α, IL-8, and VEGF in the assessment of skin wound repair and regeneration 180 Furthermore, encouraging research signifies that gemifloxacin mitigates TNF-α-mediated NF-κB stimulation, lymphocyte penetration, and recruitment. 181 In another investigation, gemifloxacin also modified the immune response utilizing normal adult monocytes by suppressing monocytic liberation of IL-1β, IL-6, and TNF-α.…”
Section: ■ Discussionsupporting
confidence: 86%
“…Cellular migration and invasion are the main features of tumor biology and play a pivotal role in metastasis, which is a major determinant of oncological patients’ death [ 61 ]. Published studies reported the anti-migratory nature of quinolone compounds in different cell lines, an effect related to their ability to inhibit metalloproteinase expression [ 28 , 33 , 62 ]. In agreement with these studies, our results highlighted that, similarly to CIP and NOR, their derivatives significantly inhibited cell migration and induced a general decrease in MMP2 and MMP9 protein levels, with better performances against MMP2 (except for MDA-MB453 cells).…”
Section: Discussionmentioning
confidence: 99%
“…In general, there seems to be consensus that reducing the zwitterionic character or increasing lipophilicity can result in a better antitumor effect [ 26 , 27 ]. Several derivatives of ciprofloxacin (CIP) and norfloxacin (NOR) have recently been shown to exhibit more potent antitumor activity than the parent compounds in various cancer cell lines [ 3 , 14 , 28 ]. In this context, our group synthesized a panel of CIP and NOR derivatives, which showed stronger antineoplastic effects in tumor cell lines of different tissue origin, also evidencing a higher extent of interaction with topoisomerase II, compared to the two precursors [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[116][117][118] For example, various proangiogenic substances, such as fibroblast growth factor (FGF), matrix metallopeptidase 9 (MMP-9), and vascular endothelial growth factor (VEGF), are produced by TAMs to promote tumor progression and metastasis in various cancers, including osteosarcoma. [119][120][121] Moreover, TAMs can also interact with various immune effector cells to induce an immunosuppressive tumor microenvironment. They can suppress the activity of T lymphocytes to facilitate tumor immune escape by overexpressing PD-1 and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) receptors.…”
Section: The Immune Microenvironment Of Osteosarcomamentioning
confidence: 99%